PENGARUH BRAND ORIGIN, BRAND AMBASSADOR DAN BRAND IMAGE TERHADAP MINAT BELI PARFUM AXE (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Jurusan Manajemen Universitas Islam Malang) - Muhammad Shohibul Munir; Nurhajati Nurhajati; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTACT This research was conducted at University Islamic of Malang. In this study, the aim is to find out the influence of brand origin, brand ambassadors and brand image on buying interest in axes on students of the Faculty of Economics and Business Department of Management at the Islamic University of Malang. The variables used in this study are brand origin, brand ambassador and brand image as variables independent then buying interest as the dependent variable. The sample in this study amounted to 80 respondents. Sampling using purposive sampling. The method of data collection in this study used a questionnaire. The analysis used in this study includes the instrument test, normality test, classic assumption test, multiple linear regression test and hypothesis testing using the help of SPSS 16.0 for Windows software. Keywords: brand origin, brand ambassador, brand image and buying interest